The relationship between anxiety levels and smoking behaviour among high school students - Ariyantika, Feby; Triyoso, Triyoso; Furqoni, Prima Dian (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Adolescence is a transition period that is vulnerable to changes in emotions and behavior, including anxiety and smoking behavior. Indonesia is the 5th country with the highest smoking rate in the world, in 2023 the Indonesian health survey states that more than 70 million smoke. In Lampung in 2022 there will be 87.01% smokers. Purpose: To find out the relationship between anxiety levels and smoking behavior among teenagers. Method: This type of research uses a quantitative research method with a cross-sectional approach, total sampling technique. The analysis in this study is univariate and bivariate analysis with the chi-square test and Spearman's rho. The population and sample in this study were all male students in grades X-XI at Senior High School Persada Bandar Lampung, totaling 49 students. Results: The level of anxiety of the majority was in the moderate category, namely 17 respondents (35%) and for smoking behavior, the majority were in the high category, 17 respondents (35%). After the chi-square test was carried out, the p-value was obtained at 0.000 <0.05 and the Spearman's rho test obtained a correlation coefficient value of 0.954, meaning that there was a relationship between the level of anxiety and smoking behavior and the correlation between the two variables was very strong. Conclusion: There is a significant and very strong relationship between anxiety levels and smoking behavior. It is hoped that schools can develop educational programs in the form of anxiety and smoking behavior prevention programs through group counseling, health education about the dangers of smoking and anxiety management training. Keywords: Adolescents; Anxiety; Smoking Behavior.